A multi-objective programming approach for designing complicated logistics network. Issue 4 (1st January 2011) - Zhou, Lina; Xu, Xiaofei; Deng, Shengchun
Designing logistics network is a crucial and frequent decision for manufacturers, particularly for those operating in large developing countries. The majority of the existing logistics network models are single objective and the optimisation objective is usually minimising cost. However, multiple and conflicting objectives usually need to be considered in designing a real-life logistics network. In this paper, a complicated logistics network design problem is mathematically formulated as a multi-objective programming model and a goal attainment based solution procedure is proposed. An example is given in the end, which introduces the application of the proposed approach in a practical problem.